Ludobójstwo Jezydów w północno-zachodnim Iraku - aspekty prawne i kulturowe - Wojciech Kaczor (Przegląd Geopolityczny, 2021)
Article discusses the legal and cultural aspects of the genocide perpetrated by the Islamic State on the syncretic Yezidi minority inhabiting north-western Iraq. Such issues as mass killings, sexual violence and indoctrination of children are being confronted with the regulations of the 1948 Genocide Convention, interpreted according to the jurisprudence of international tribunals.